Ecologia e comportamento do bugio vermelho (Alouatta puruensis) em um fragmento florestal em Rolim de Moura, Rondônia - Quintino, Erika Patrícia (2014)
Forest loss and fragmentation affect habitat quality for arboreal species. Among New World monkeys, howlers (Alouatta spp.) stand out for their ability to survive in fragmented and human-altered forests. This dissertation reports the results of the first study on the ecology and behavior of the Purús red howler monkey (Alouatta puruensis). A social group composed of seven individuals (an adult male, three adult females, a subadult male, a juvenile male, and an infant male) was observed from dawn to dusk during six 15-day periods (=90 days of sampling effort or 1,044 hours of observation) from April to October 2013 in a 2,2-ha forest fragment in Rolim de Moura, state of Rondônia, Brazil. The behavior of the study subjects was recorded using the instantaneous scan sampling method. The study group spent most of the day resting (69% of records), followed by moving (17%) and feeding (12%), and fed on a predominantly folivorous diet (61% of feeding records) that was complemented with flowers (23%) and fruits (15%) belonging to, at least, 36 species. The group ranged over the entire area of the fragment and traveled between 257 and 860 m each day. Quadrupedal walking was by far the most common locomotor mode (97% of records) and sitting was the most common feeding (53%) and resting (57%) posture. The type of food influenced the use of feeding postures. The howlers also adopted a thermoregulatory behavior during resting, increasing the use of heat dissipating postures and the selection of shady places with increasing ambient temperatures. This research also produced the first report of a predation event of a howler monkey by a snake (boa Boa constrictor). In sum, Purús red howler monkeys (A. puruensis) show a behavioral pattern characteristic of the genus.